Gender Equality Among CSR Managers and its Influence on Sustainable Development: A Comparison Among Italy, Spain and United Kingdom - Calabrese, Armando; Costa, Roberta; Levialdi Ghiron, Nathan; Menichini, Tamara (European Journal of Sustainable Development, 2018)
The Sustainable Development Goals (SDGs) of the United Nations’ 2030 Agenda for Sustainable Development are intended to orientate efforts of governments and companies to deal with environmental and social problems affecting contemporary societies. Gender Equality is one of these SDGs, and the women’s participation in leadership at all levels of decision making in political, economic and public life, is one of its crucial targets. The paper analyses the progress in meeting this target with a focus on the European Union (EU) context. Particularly, a qualitative trend analysis is employed on the data from “World Bank Group” database, and the “Global 100: Most Sustainable Corporations in the World” for performing a comparison of the temporal evolution of Gender Equality in Italy, Spain and United Kingdom as countries registered in the “European Organizations of Sustainability Professions” portal. The results show that the mean female share of employment in senior and middle management is growing, and that managerial roles in CSR are a gender-virtuous field of management. Nevertheless, a question arises: is the gender equality among CSR managers an indicator of a sustainability-oriented approach to management? An analysis of Corporate Knights’s ranking of the world’s most sustainable corporations reveals that the female share of CSR managers is not directly linked to the presence of sustainable corporations. These empirical evidences arise some questions as well as some policy suggestions that will be discussed. Keywords: Gender equality; Female leadership; Sustainable Development Goals (SDGs); Sustainable Development; Corporate Social Responsibility (CSR) Manager; Sustainability